Les difficultés de la transposition communale des corridors écologiques. Analyses appliquées à trois communes de l’agglomération tourangelle - Adèle Debray (Développement Durable et Territoires)
The green and blue infrastructure (TVB) is a recent public policy entity which enroll the biodiversity conservation goal in the planning instruments, relying on complex and innovative principles (ecological corridors, functionality, etc.). Through the results of a thesis, the paper examines the transposition of ecological corridors in urban local plans. We hypothesize that these local interpretations of TVB encounter problems related to the legal powers of municipal tools concerning land use. These are hardly suitable for management of ecological issues. The study is focused on three municipalities located in Tours area, which is working on a TVB implementation since 2009.